The effect of indoor soundscape on sexual wellbeing during the COVID-19 lockdown in London: a thematic analysis of remote workers' experiences. (November 2022) - Torresin, Simone; Ratcliffe, Eleanor; Aletta, Francesco; Albatici, Rossano; Babich, Francesco; Oberman, Tin; Kang, Jian
Abstract: Background: Despite sexual wellbeing representing a potential component of the overall wellbeing of individuals, its relationship to indoor soundscape has not been investigated. The aim of this study was to identify acoustic-related variables linked to sexual wellbeing during the COVID-19 lockdown; the mechanisms through which those variables exert an influence; and the components of an ideal indoor soundscape for sexual wellbeing. Methods: We did a thematic analysis of answers to an online survey conducted on Jan 18–19, 2021, via the Prolific participant platform. The survey was completed by 464 adult individuals working at home in London during the third national COVID-19 lockdown (Jan 6 to March 8, 2021). This study focused on two optional open-ended questions concerning (1) effects of the acoustic environment on sexual activity and (2) characteristics of an ideal soundscape for best experiencing sexual intercourse. The formation of codes and themes followed a combination of inductive and deductive approaches. Findings: 345 responses were collected for question 1 (134 [39%] men, 210 [61%] women, one [<1%] other) and 310 responses for question 2 (124 [40%] men, 185 [60%] women, one [<1%] other), with a respondent age range of 18–65 years. The thematic analysis produced four themes: contextual features, characteristics of the acoustic environment, soundscape interpretation, and coping strategies. With regard to the acoustic environment, the main variables were related to the type of sound, sound dominance, and temporal patterns. Among the participants who provided relevant answers (n=239), 132 (55%) considered the acoustic environment irrelevant while being focused on the sexual activity, 72 (30%) reported negative or mixed effects, and 35 (15%) described only positive effects. Indoor soundscape resulted in privacy concerns, distraction, disruption, or support to sexual wellbeing. Soundscape interpretation triggered coping strategies (eg, adjusting windows or playing music) and behavioural changes (eg, lowering voice level), which in turn limited or increased sexual freedom, and affected or promoted sexual wellbeing. The ideal soundscape was described by three themes related to the availability of privacy and control, quietness, and pleasant sounds. Interpretation: Although this study is qualitative in nature and no causal link can be established, it highlights the influence the acoustic environment at home had on sexual wellbeing during lockdown. Funding: Chartered Institution of Building Services Engineers.